PELAKSANAAN RETRIBUSI PARKIR DI TEPI JALAN UMUM DI WILAYAH KECAMATAN TAMPAN KOTA PEKANBARU BERDASARKAN PERATURAN DAERANOMOR 3 TAHUN 2009 TENTANG RETRIBUSI PELAYANAN DIBIDANG PERHUBUNGAN DARAT - Ningsih, Fitria; Haryono, Dodi; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Parking levy is payment for the use of the service organization and use of the parking lot, which is contained in each of the places visited such as shopping centers, restaurants and entertainment venues, good parking space provided by the local government and on the edge of the public road. as there is in the area of the districts Handsome Pekanbaru order to increase revenue (PAD), One implementation Levy Parking On the Edge of the existing public road in Regional District of handsome Pekanbaru City Regional Regulation No. 3 of 2009 on Retribution Pelyan in the Field of Communications Army. The purpose of this study is: First To determine pelaksanann roadside Levy Parking In general, based on Regional Regulation No. 3 of 2009 in the District Handsome Pekanbaru. Second, to determine barriers for the implementation of the parking levy based on the edge of the public road Based on Local Regulation No. 3 of 2009 in the District Handsome Pekanbaru. Third, To know the effort that can be done to overcome the obstacles in the implementation of roadside parking levies generally based on Regional Regulation No. 3 of 2009 in the District Handsome Pekanbaru.This study is a kind of sociological research or empirical jurisdiction. Location of the study is the Regional District of Handsome Pekanbaru. Source of data, supported by the primary data source, secondary data sources, data source tartier, while the data collection techniques are interviews, questionnaires and library studies. After the data collected was then analyzed qualitatively using the deductive method to analyze the problems of a general nature and is then drawn to a conclusion in particular based on existing theory.From the research problem there are three things that can be inferred, first implementation of curbside parking fees in general, based on Regional Regulation No. 3 of 2009 in the subdistrict of Pekanbaru City Handsome not performing as it should be because of the lack of socialization of the local government to arkir officers and lack of coordination between government the field coordinator. This is because of the barriers faced by local governments. Both the obstacles faced in the implementation of roadside parking levies common in Pekanbaru City Regional District of Handsome operational shortage of officers involved in the supervision and inspection of the field to the parking attendant who sometimes banyaak parking attendant who do not have official permission to carry out their duties.Keywords:Retribusi- Local Revenuelocally-generated revenue